Complementation of intramolecular interactions for structural-functional stability of plant serine proteinase inhibitors - Joshi, Rakesh S.; Mishra, Manasi; Suresh, C. G.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Plant protease inhibitors (PIs) constitute a diverse group of proteins capable of inhibiting proteases. Among Pls, serine Pls (SPIs) display stability and conformational restrictions of the reactive site loop by virtue of their compact size, and by the presence of disulfide bonds, hydrogen bonds, and other weak interactions. Scope of review: The significance of various intramolecular interactions contributing to protein folding mechanism and their role in overall stability and activity of SPIs is discussed here. Furthermore, we have reviewed the effect of variation or manipulation of these interactions on the activity/stability of SPIs. Major conclusions: The selective gain or loss of disulfide bond(s) in SPIs can be associated with their functional differentiation, which is likely to be compensated by non-covalent interactions (hydrogen bonding or electrostatic interactions). Thus, these intramolecular interactions are collectively responsible for the functional activity of SPIs, through the maintenance of scaffold framework, conformational rigidity and shape complementarities of reactive site loop. General significance: Structural insight of these interactions will provide an in-depth understanding of kinetic and thermodynamic parameters involved in the folding and stability mechanisms of SPIs. These features can be explored for engineering canonical SPIs for optimizing their overall stability and functionality for various applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Disulfide bond; hydrogen bonding; Intramolecular weak interaction; Protease; Reactive site loop; Serine proteinase inhibitor

Cathepsins of lepidopteran insects: aspects and prospects - Saikhedkar, Nidhi; Summanwar, Aarohi; Joshi, Rakesh S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2015)
Molecular understanding of lepidopteran physiology has revealed that proteases consist of one of the central regulatory/reacting system for insect growth and survival. Among the various proteases, cathepsins are the most crucial cellular proteases, which play vital roles during insect development. In the present review, we have discussed various aspects of the lepidopteran insect cathepsins, emphasizing their roles in processes like development, growth, metamorphosis, apoptosis and immunity. Cathepsins are categorized into different types on the basis of their sequence diversification, leading to variation in structure and catalytic function. Cathepsins exhibit tissue and stage specific expression pattern which is fine-tuned by a delicate balance of expression, compartmentalization, zymogen activation, inhibition by protein inhibitors and degradation. The indispensability of cathepsins as cellular proteases in the above mentioned processes proposes them as novel targets for designing effective and specific insect controlling strategies. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Cathepsin; Cysteine/aspartate protease; Development; Lepidoptera; Pest control; Stress response

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Cyclic peptide engineered from phytocystatin inhibitory hairpin loop as an effective modulator of falcipains and potent antimalarial - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Pandey, Kailash C.; Singh, Shailja (Journal of Biomolecular Structure & Dynamics, 2022)
Cystatins are classical competitive inhibitors of C1 family cysteine proteases (papain family). Phytocystatin superfamily shares high sequence homology and typical tertiary structure with conserved glutamine-valine-glycine (Q-X-V-X-G) loop blocking the active site of C1 proteases. Here, we develop a cysteine-bounded cyclic peptide (CYS-cIHL) and linear peptide (CYS-IHL), using the conserved inhibitory hairpin loop amino acid sequence. Using an in silico approach based on modeling, protein-peptide docking, molecular dynamics simulations and calculation of free energy of binding, we designed and validated inhibitory peptides against falcipain-2 (FP-2) and -3 (FP-3), cysteine proteases from the malarial parasite Plasmodium falciparum. Falcipains are critical hemoglobinases of P. falciparum that are validated targets for the development of antimalarial therapies. CYS-cIHL was able to bind with micromolar affinity to FP-2 and modulate its binding with its substrate, hemoglobin in in vitro and in vivo assays. CYS-cIHL could effectively block parasite growth and displayed antimalarial activity in culture assays with no cytotoxicity towards human cells. These results indicated that cyclization can substantially increase the peptide affinity to the target. Furthermore, this can be applied as an effective strategy for engineering peptide inhibitory potency against proteases.
Keywords: Cyclic peptide; falcipain inhibitors; falciparum; P; Phytocystatin; protein interaction mimics; protein&#8211